Clinical Profile of Scleritis in Children. (19th May 2019) - Majumder, Parthopratim Dutta; Ali, Sowkath; George, Amala; Ganesh, Sudha; Biswas, Jyotirmay
ABSTRACT: Purpose : To describe the clinical pattern of scleritis in patients ≤16 years of age at a tertiary care eye hospital in India. Methods : The medical records of 24 eyes of 20 children with scleritis were included in this retrospective study. Collected data included age, subsets of uveitis, best corrected visual acuities (BCVA), detailed laboratory investigations and treatment. Results : Mean age at presentation was 12.2 ± 2.5 years. Scleritis was unilateral in 80% patients and an equal gender distribution was observed. Posterior scleritis (41.7%) was the most common subtypes of scleritis and nodular scleritis was the most common type of anterior scleritis (33.3%). Necrotizing scleritis was seen in 16.7% eyes. Tuberculosis was the only systemic association and found in three (15%) patients. Conclusions : Clinical profile of scleritis in children can be different from that of adults.